Contribution of socio-demographic and structured leisure activities’ characteristics to adolescents’ alcohol use - Belošević, M; Ferić, M (Adiktologie, 2022)
BACKGROUND: Leisure can be a context that can promote positive adolescent development, but it can also be a context that contributes to adolescents engaging in risk behaviours. AIMS: The aim of this study is to determine the extent to which sociodemographic characteristics, the frequency of adolescent participation in structured leisure activities (SLA), and the type of SLA contribute to adolescent alcohol use and to examine the moderating effects of gender, age, and type of SLA on the relationship between the frequency of adolescent participation in SLA and adolescent alcohol use. METHODS: The study was conducted from April to June 2021 as part of a research project examining leisure and risk behaviours in Croatia. The sample consisted of students who reported having participated in SLA (N = 1431). The participants were between 14 and 21 years old (44.8% female). The Questionnaire of Youth Leisure Time and the CTC Youth Survey were used. Multinomial logistic regression analysis and Poisson regression were used to achieve the aim of this article. RESULTS: The results indicate that gender, age, and the type of SLA have an influence on adolescent alcohol use. Males and older adolescents who participated in SLA used more alcohol. The type of SLA in which adolescents participate influences the pathway of alcohol use. In addition, the results confirmed the moderating effect of the type of SLA on the relationship between the frequency of adolescent participation resulting from the constraints imposed by the COVID-19 pandemic and adolescent alcohol use. Accordingly, more frequent participation in group sports, performance/fine arts, and educational activities acts as a protective factor and reduces the likelihood of risky alcohol use, whereas more frequent participation in community-oriented activities acts as a risk factor and increases the likelihood of risky alcohol use. CONCLUSIONS: When planning and implementing preventive interventions within the leisure context, it is important to consider that gender, age, and the type of SLA may influence the risk of adolescent alcohol use, and interventions need to take these findings into account to be effective.